Жанри офіційно-ділової комунікації в релігійному дискурсі - Дрофяк, Б. (Культура слова, 2020)
У статті здійснено аналіз офіційно-ділових документів, які використовують у релігійній сфері. Визначено жанри, структуру і функціонування офіційно-ділових текстів сучасного релігійного дискурсу. Розглянуто вербальні та невербальні засоби ділової комунікації. The development of an independent conciliar Ukrainian state and the related processes of restoring historical memory, awakening of national consciousness raised the issue of the functioning of the Ukrainian language in the church, drew public attention to the development of the religious style of the Ukrainian literary language. Like any other public structure, church communicates at the internal religious (confessional) level and at the external - national level. This leads to the formation and establishment of official-business language communication, operation of documents that have characteristic linguisticstructural (lexical, syntactic, textual) features, different from the usual office work. The documentation of the activities of religious organizations reflects the following main stages: - Establishment of religious organizations: statement, charter of the religious community, minutes of the general meeting on the adoption of the statute (regulations) and elections of governing (executive) bodies, a document confirming the organizational and canonical subordination of the religious community, etc. - Staffing: decree. - Participation in the Sacraments: Certificate of Holy Matrimony, Certificate of Baptism and Holy Chrismation, Certificate of Ordination. - Honouring with liturgical and church awards and distinctions. Priests are rewarded with liturgical awards according to the hierarchy of promotion. After that, together with the award, the clergy receive an official document - a Certificate. In addition, there are a number of church awards. Among them are diplomas, orders, medals, which are conferred to lay people who work for the good and prosperity of the Orthodox Church. - Formal business communication for different needs. According to the classification of S. Honhalo, the documents are divided into: - by name: orders, instructions,prescriptions, reports, statements, notes, letters, invitations, etc; - by place of drafting: internal and external; - by origin: official and official personal; - by purpose: originals and copies. - Confirmation of facts: Reference. Having identified the genres, structure and functioning of official business communication in religious discourse and analyzed them, we can conclude that these documents do not have a high level of standardization, clear structure and rules of design in accordance with legal requirements. They need a clear classification of documents of religious style, the development of requirements for their design, in general – the standardization and unification of official business texts of religious discourse.